The Role of Saving and Credit Cooperatives in Improving Household Income: The Case for Teachers in Iganga District - Albert Chawanga (Uganda Christian University, 2025)
Savings and Credit Cooperative Societies (SACCOs) have emerged as critical tools for promoting financial inclusion and income enhancement, especially in rural areas of Uganda. This study explores their role in improving household income among teachers in Iganga District. The objective was to assess how SACCO services—namely loan provision, savings mobilization, and financial advisory—affect the economic welfare of teachers. A mixed-methods approach was employed, incorporating cross-sectional surveys, structured interviews, and analysis of secondary data from SACCO reports and school records. The results showed that 70% teachers accessed SACCO loans, mainly for income-generating activities, with a significant majority (82%) of regular savers reporting enhanced financial stability. Financial advisory services improved financial literacy, though inconsistent delivery hindered their overall impact. Regression analysis showed a strong positive correlation between loan access and income growth (r = 0.94, p < 0.01). Despite these benefits, challenges such as weak governance and limited product flexibility were identified. The study concludes that SACCOs substantially enhance household income among teachers, but reforms in governance and service delivery are essential for sustainable impact. Keywords: SACCOs, household income, financial inclusion, microfinance, Uganda, teacher welfare